Feasibility analysis of neutral grounding by small reactor of HVDC converter transformer - Ensheng Zhao (Elsevier, 2022)
Nowadays, the scale of power grid is remarkably increasing and there is a continuous reinforcement of AC–DC hybrid systems. Thus, the single-phase grounding fault currents on the AC grid-side of rectifier and inverter stations increase significantly, which may exceed the capacity limit of the circuit breakers. The large short-circuit currents would result in problems during equipment selection and threaten the safety of equipment and personnel. To solve such issue, the effect of the converter transformer on the single-phase grounding fault current on the grid-side is analyzed. The mechanism of high short-circuit current in DC near region is revealed. Also, the feasibility of neutral point earthing via small reactor at HVDC converter transformer to suppressing the single-phase grounding fault current is verified. In addition, the principle of selecting the suitable small reactor is summarized. The results show that the neutral point earthing via small reactor at converter transformer can effectively limit the single-phase grounding fault current on the AC-side. However, it would lead to an increase of overvoltage at the neutral point of HVDC transformer. Therefore, neutral grounding by small reactor might be implemented when the insulation level is satisfied.